A Brief Analysis of the Brazilian Institute of Forestry Development (1967-1989): between development and the forest (Research, Society and Development, 2023)
This article sought to address the clashes between developmentalist and conservationist perspectives within the Brazilian Institute of Forestry Development (IBDF) through the actions of its directors, seeking to identify their interests and the disputes of the projects that were at stake. Therefore, in addition to the bibliographic review on the subject, it was of fundamental importance to use the Hemeroteca Nacional Digital collection as a way of identifying the agents involved in the institute, their respective actions and the conflicts arising from this. In this way, we understand the State as the result of the conflicting relationship between different class fractions, and not merely as a regulatory body that aims at the common good, or that is a mere instrument of a dominant class. Within the IBDF, agricultural and developmental expansion was opposed by conservationist sectors, while it was encouraged by business groups. The contradiction between development and the forest ran through the entire period of existence of the autarchy, until its end due to its ineffectiveness, both in relation to economic development and nature conservation.